Digitalization on Micro, Small, and Medium Enterprises (MSMEs) : A Systematic Literature Review - Panduwinata, Lifa Farida; Subroto, Waspodo Tjipto; Sakti, Norida Canda (International Journal of Economics, Commerce, and Management, 2025)
This research explores the impact of digitalization on Micro, Small, and Medium Enterprises (MSMEs) using a systematic literature review (SLR) approach based on the PRISMA method. The data collection process began with the identification of relevant scientific articles using the keywords "digitalization," "MSMEs," and "digital transformation," through leading academic databases, such as Scopus, Google Scholar, and JSTOR. The initial search identified 278 articles, of which 35 met the predetermined inclusion criteria. A thorough analysis of these 35 articles revealed that digitalization plays a pivotal role in fostering innovation within the MSME sector, offering benefits such as enhanced operational efficiency, expanded market access, and strengthened social, economic, and environmental sustainability. However, the implementation of digitalization in MSMEs is encumbered by several challenges, including limited resources, uneven digital infrastructure, and cyber security threats. The study underscores the significance of the government's role in establishing regulatory frameworks, offering financial incentives, and fortifying infrastructure to facilitate the sustainable digital transformation of MSMEs. This research provides strategic insights for policymakers, practitioners, and academics, offering guidance on the successful adoption of digitalization in the MSME sector.